Seroprevalence study results to SARS-CoV-2 in healthcare workers: age and professional aspects - E. V. Agafonova; S. N. Kulikov; I. D. Reshetnikova; Yu. A. Tyurin; G. F. Gilyazutdinova; D. V. Lopushov; N. D. Shaуkhrazieva; G. Sh. Isaeva; V. B. Ziatdinov (Эпидемиология и вакцинопрофилактика)
Relevance. Age-related and occupational aspects of SARS-CoV-2 seroprevalence in healthcare workers are not well understood. Aims: Conduct a selective study of seroprevalence to the SARS-CoV-2 virus among 348 medical workers of 10 medical organizations in Kazan: seven multidisciplinary hospitals that have been re-profiled to provide medical care to patients with coronavirus infection, an ambulance station, a medical organization that carries out outpatient activities and a specialized clinic. Materials and methods. Among those surveyed on a professional basis, the groups «Doctors», «Nurses», «Junior medical personnel», «Other medical workers» were identified. The age structure of seroprevalence was studied in groups of 18–29, 30–39, 40–49, 50–59 and 60–69 years. For the determination of IgG, a solid-phase ELISA was used. Results. The proportion of medical workers (MR) of various medical organizations in Kazan seropositive for IgG to the SARS-CoV-2 virus is 16.4%. The wide variation in the seroprevalence value of MR groups of different medical organizations (3.3–30.8%) may indicate a different level of effectiveness of anti-epidemic measures in these institutions. The maximum rate was noted in the age groups – 18–29 years (21%) and 60-69 years (18.2%). According to the professional criterion, a comparable level of seroprevalence is shown for the categories «Doctors» and «Nurses» with a wide variation in indicators in professional groups, depending on a particular medical organization. The obtained results indicate the presence among medical workers who have suffered or have an asymptomatic course of infection caused by SARS-CoV-2, and confirm the relevance of further serological monitoring in medical organizations of various profiles. The results of serological monitoring, taking into account age and professional aspects, can serve as the basis for adjusting preventive measures on the basis of individual medical organizations, and taking into account the recommendations of Rospotrebnadzor and the selection of contingents for vaccination against SARS-CoV-2. Conclusions: For the MR of various medical institutions in Kazan, the seroprevalence for antibodies to the SARS-CoV-2 virus is 16.4%; Age aspects affect the level of seroprevalence in MR; The obtained results indicate the presence of persons among MR who have had or have an asymptomatic course of infection caused by SARS-CoV-2, and confirm the relevance of further serological monitoring in medical organizations of various profiles.